Am I Overweight? A Longitudinal Study on Parental and Peers Weight-Related Perceptions on Dietary Behaviors and Weight Status Among Adolescents - Zarychta, Karolina; Mullan, Barbara; Luszczynska, Aleksandra (Frontiers in Psychology, 2016)
Objective: An investigation of the interplay between various types of adolescents’ perceptions of weight status in predicting adolescents’ nutrition behavior and their body weight was conducted. In particular, it was hypothesized that the relationship between parental and peers’ perceptions of their own weight status (reported by adolescents) and objectively measured weight status of adolescents would be mediated by three types of adolescents’ weight status perceptions (adolescents’ own weight perceptions, parental perceptions of adolescents’ weight status perceived by participants, and peers’ perceptions of adolescents’ weight status perceived by participants) and by adolescents’ nutrition behaviors. Design: Data were collected twice, with a 13-month follow-up. Participants (N = 1096) were aged 14-20, with BMI ranging from 16.20 to 41.21. Multiple mediation analysis with two sequential mediators was applied. Main outcome measures: At the baseline adolescents completed the questionnaire assessing their nutrition behaviors and weight status perceptions. Weight and height were measured objectively at baseline and follow-up. Results: Two types of weight perceptions (adolescents’ own weight status perceptions, peers’ perceptions of adolescents’ weight status reported by participants), and adolescents’ nutrition behaviors mediated the relationship between the others’ own weight perceptions and adolescents’ weight status. No indirect effects of others’ own weight perceptions on adolescents’ weight status through parental perceptions were found. Conclusion: Adolescents’ nutrition behaviors and body weight status depend on what they think about their own weight status and what they think of their peers’ perceptions, but do not depend on what adolescents think of their parents’ perceptions.